A Critical Role of Bacterioferritin in Salmonella pullorum-Induced IFN-β Expression in DF-1 Cells - Xu, Zhichao; Qin, Yao; Wang, Yongqiang; Li, Xiaoqi; Cao, Hong; Zheng, Shijun J. (Frontiers in Microbiology, 2016)
Salmonella enteric serovar Pullorum (S. pullorum) causes pullorum disease in poultry and results in great economic losses to poultry industry. Although eradication program has been successfully performed in some countries, it remains a major threat to countries with poor poultry disease surveillance and no effective control measures. In particular, the pathogenesis of S. pullorum infection is still largely unknown. Here we show that bacterioferritin (Bfr) was indentified as an immunodominant antigen of S. pullorum to elicit humoral immune response. Furthermore, we demonstrate that Bfr induces activation of IFN-β promoter and mRNA expression in DF-1 cells, and the amino acids 1-50 of Bfr is a critical domain involved in IFN-β expression. Moreover, we found that the p38 MAPK signaling pathway was essential for Bfr-induced IFN-β expression. Importantly, S. pullorum induced-IFN-β was totally abolished by deficiency of Bfr in the bacteria, indicating that Bfr plays a critical role in S. pullorum induced-IFN-β expression in DF-1 cells. Our findings provide new insights into the molecular mechanisms of the host response to S. pullorum infection.